2015
DOI: 10.1097/jnr.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Sleep Quality and Chronotype, Emotional Disturbance, and Insomnia Vulnerability in Shift Nurses

Abstract: In addition to shift patterns, emotional disturbance and high insomnia vulnerability are factors that may be used to identify shift nurses who face a higher risk of sleep disturbance. Because evening chronotype may indirectly influence subjective sleep quality through the pathway of emotional disturbance, further research into the mechanism that underlies this pathway is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 26 publications
4
38
0
5
Order By: Relevance
“…This finding was in agreement with that of Alshahrani et al in which Saudi Arabia shift nurses significantly reported a higher score for these three components [25]. The poor sleep quality of ICU nurses was related to the "Sleep latency" and "Daytime dysfunction" [30]. Daytime dysfunction and sleep disturbances could make contribution to daily disturbances.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was in agreement with that of Alshahrani et al in which Saudi Arabia shift nurses significantly reported a higher score for these three components [25]. The poor sleep quality of ICU nurses was related to the "Sleep latency" and "Daytime dysfunction" [30]. Daytime dysfunction and sleep disturbances could make contribution to daily disturbances.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also revealed that 71.3% of nurses reported poor sleep quality. Several previous studies supported this finding and indicated that more than 70% of nurses had poor sleep quality (Chien et al, ; Lee, Chen, Meg Tseng, Lee, & Huang, ; Lin et al, ; Weaver et al, ). Although many factors are known to lead to poor sleep quality, our findings confirmed that poor sleep quality is a common health problem in hospital nurses.…”
Section: Discussionsupporting
confidence: 53%
“…Nurses with the best sleep quality worked a two-shift rotation and on the other two types of shift rotation (three-shift fast rotation and night-shift rotation), nurses were diagnosed with insomnia (AIS scores > 6). Prior research has reported that insufficient sleep and poor sleep quality impact metabolism, the immune system, and the digestive system resulting in psychophysiological health problems such as emotional disturbances [19,20]. Other studies have shown that the better the sleep at night, the greater the daytime alertness [21], meaning that in this study daytime alertness was higher when nurses were on the two-shift fast rotation pattern as opposed to the other two.…”
Section: Discussionmentioning
confidence: 64%